The promoter of miR-663 is hypermethylated in Chinese pediatric acute myeloid leukemia (AML) - Yan-Fang, Tao (BioMed Central, 2013)
BACKGROUND: There is growing evidence supporting a role for microRNAs (miRNA) as targets in aberrant mechanisms of DNA hypermethylation. Epigenetic silencing of tumor suppressor miRNAs, including miR-663, which has recently been reported to be inactivated by hypermethylation in several cancers, may play important roles in pediatric acute myeloid leukemia (AML). However, expression of miR-663 and its promoter methylation remain status unclear in childhood leukemia. METHODS: Promoter methylation status of miR-663 was investigated by methylation specific PCR (MSP) and bisulfate genomic sequencing (BGS). Transcriptional expression of miR-663 was evaluated by semi-quantitative and real-time PCR, and the relationship between expression of miR-663 and promoter methylation was confirmed using 5-aza-2’-deoxycytidine (5-Aza) demethylation reagent. RESULTS: MiR-663 was aberrantly methylated in 45.5% (5/11) leukemia cell lines; BGS showed that the promoter was significantly methylated in three AML cell lines; methylation of miR-663 was significantly higher in Chinese pediatric AML patients [41.4% (29/70)] compared to normal bone marrow (NBM) control samples [10.0% (3/30)]. These results were confirmed by both BGS and 5-Aza demethylation analysis. In addition, miR-663 transcript expression was significantly lower in AML patients, both with and without miR-663 methylation, compared to controls; however, there were no significant differences in clinical features or French-American-British (FAB) classification between patients with and without miR-663 methylation. CONCLUSIONS: Expression of miR-663 was significantly lower in pediatric AML cells compared to NBM controls; furthermore, a high frequency of miR-663 promoter hypermethylation was observed in both AML cell lines and pediatric AML samples. Inactivation of miR-663 by promoter hypermethylation could be affected by 5-Aza demethylation. These findings suggest that hypermethylation of the miR-663 promoter may be an early event in the development of pediatric AML.